2009
DOI: 10.1021/bi9006995
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Incorporation of the Fluorescent Cytosine Analogues tC and tCo by Human DNA Polymerase α and Klenow Fragment

Abstract: We studied the incorporation of the fluorescent cytidine analogues 1, 3-diaza-2-oxo-phenothiazine (tC) and 1, 3-diaza-2-oxo-phenoxazine (tCo) by human DNA polymerase α and Klenow fragment of DNA polymerase I (E. coli). These tricyclic nucleobases possess the regular hydrogen bonding interface of cytosine but are significantly size expanded toward the major groove. Despite the size alteration both DNA polymerases insert dtCTP and dtCoTP with remarkable catalytic efficiency. Polymerization opposite guanine is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 51 publications
5
60
0
Order By: Relevance
“…DinB synthesizes DNA up to and across from tC, accurately incorporating G, but cannot efficiently bypass tC. It has also been observed that tC can tautomerize to a form that base pairs with A; 41,42 however, similar to human DNA primase and RNA polymerase, 42,43 we did not observe misincorporation by DinB. The tC analog is known to be bypassed by the A-family polymerase Klenow fragment, as well as by human DNA polymerase α primase.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…DinB synthesizes DNA up to and across from tC, accurately incorporating G, but cannot efficiently bypass tC. It has also been observed that tC can tautomerize to a form that base pairs with A; 41,42 however, similar to human DNA primase and RNA polymerase, 42,43 we did not observe misincorporation by DinB. The tC analog is known to be bypassed by the A-family polymerase Klenow fragment, as well as by human DNA polymerase α primase.…”
Section: Discussionmentioning
confidence: 55%
“…The tC analog is known to be bypassed by the A-family polymerase Klenow fragment, as well as by human DNA polymerase α primase. 28,41 Specifically, the Klenow fragment accurately inserts dGTP opposite template tC 28 and can then extend the primer to the end of the template. 41 Remarkably, the Klenow fragment is also fairly proficient at bypassing 8-oxo-G and C 8 -aminofluorene-dG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a short turn connecting ␣-helices ␣B and ␣C, together with the adjacent helix parts (Ser 40 -Leu 47 ), is inserted into the minor groove of the DNA double helix to push the damaged nucleotide out. The void left after the eversion is filled by Gln 42 , and the adjacent bases are stacked against its side chain amide group (the 3Ј-base) and the planar peptide bond Gln This arrangement of DNA and protein residues provides insights into the conformational transition dynamics associated with the changes in fluorescence of the reporters incorporated into DNA (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…The oxoG base is then fully placed into the active site and forms specific interactions within the base recognition pocket detected in the structure of the pre-catalytic hOGG1-DNA complex (22). In addition, Asn 149 (corresponding to Gln 42 in G. stearothermophilus Endo III, Fig. 3B) forms a hydrogen bond between the amide carbonyl of its side chain and the amino group of the opposite cytosine.…”
mentioning
confidence: 99%